An investigation into An Giang province high school english tearchers' views on teaching mixed-ability classes: their problems and solutions : - Nguyễn, Văn Phong Vũ (Trường đại học Cần Thơ, 2010)
The study aims at: (a) Investigating teachers' attitudes and perceptions on teaching mixed ability class; (b) seeking for the extent to which the teachers have handled with the problems identified.